Development of Wide-Compatible Indica Lines by Pyramiding Multiple Neutral Alleles of Indica–Japonica Hybrid Sterility Loci - Guo, Jie; Li, Yun; Xiong, Liang; Yan, Tingxian; Zou, Jinsong; Dai, Ziju; Tang, Guang; Sun, Kangli; Luan, Xin; Yang, Weifeng; Tan, Quanya; Zhu, Haitao; et al. (Frontiers in Plant Science, 2022)
Since the development of indica hybrid rice in the 1970s, great success has been achieved in hybrid rice production in China and around the world. The utilization of inter-subspecific indica–japonica hybrid rice has always been considered due to its stronger heterosis characteristics. However, indica–japonica hybrids face a serious problem of sterility, which hinders the exploitation of their heterosis. In the past decades, the genetic basis of indica–japonica hybrid sterility has been well studied. It was found that in sterile indica–japonica hybrids, female sterility was mainly controlled by the S5 locus and male sterility by the Sa, Sb, Sc, Sd, and Se loci. In this study, we developed wide-compatible indica lines (WCILs) by pyramiding multiple neutral (n) alleles of the hybrid sterility loci. First, we identified Sn alleles of the loci in single-segment substitution lines (SSSLs) in the genetic background of indica Huajingxian 74 (HJX74). Then, the Sn alleles of S5, Sb, Sc, Sd, and Se loci in SSSLs were pyramided in the HJX74 genetic background. The WCILs carrying Sn alleles at the S5, Sb, Sc, Sd, and Se loci showed wide compatibility with indica and japonica rice varieties. Therefore, the WCILs will be used to develop inter-subspecific indica–japonica hybrid rice with normal fertility.